2004
DOI: 10.1039/b409364j
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of optical properties with structure of immoblised nanoparticles—a method for probing the mechanism of SERRS

Abstract: A combined surface enhanced resonance Raman scattering (SERRS) and transmission electron microscopy (TEM) method has been developed allowing the same immobilised nanoparticles to be reliably located and studied by both techniques. The method allows large numbers of particles to be analysed by each technique relatively simply and the distribution of Raman enhancement between particles and clusters, as well as the relationship between particle microstructure and Raman enhancement, to be investigated. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 16 publications
0
45
0
Order By: Relevance
“…Spectral fluctuations observed in SERS experiments were promptly attributed to single molecules effect [3][4][5], possibly overlooking the contribution due to analyte decomposition occurring by laser damage [6][7][8]. Similarly, a blinking behavior has also been readily observed in TERS experiments on dye molecules and has been interpreted as a signature of single molecule response [9][10][11].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Spectral fluctuations observed in SERS experiments were promptly attributed to single molecules effect [3][4][5], possibly overlooking the contribution due to analyte decomposition occurring by laser damage [6][7][8]. Similarly, a blinking behavior has also been readily observed in TERS experiments on dye molecules and has been interpreted as a signature of single molecule response [9][10][11].…”
Section: Introductionmentioning
confidence: 89%
“…Surface contaminating carbon may be also formed by photo-degradation of the sample due to the giant electromagnetic field in both SERS and TERS. As shown by Khan et al [6], high laser power can cause heating and burning of the sample during the spectral acquisition. Thus, complex spectra, originating from a range of intermediate surface species, may be observed.…”
Section: Introductionmentioning
confidence: 97%
“…The advantages of using minimal laser power have been demonstrated many times in SERS experiments, particularly in cases where there is a chance of molecular resonance or photochemistry. [105][106][107] One method for reducing laser-induced molecular degradation is to lower the sample temperature. For example, by conducting SERS experiments at 40 K, Pang et al [108] have shown that the negative effects of laser exposure can be greatly reduced.…”
Section: à2mentioning
confidence: 99%
“…The origins of this contamination are not fully understood, however such factors as photo-induced or thermal decomposition of the analyte molecules are usually discussed in the literature. 17 Another possible source of carbon contamination is adsorption of airborne hydrocarbons on the metal surface. 18 Other components of our assay such as antibodies and proteins may all contribute to the appearance of the carbonaceous peaks upon their decomposition.…”
Section: Resultsmentioning
confidence: 99%